Mesoporous Silica: A Perfectly Periodic Three‐Dimensional Protein/Silica Mesoporous Structure Produced by an Organism (Adv. Mater. 11/2014). (March 2014) - Zlotnikov, Igor; Werner, Peter; Blumtritt, Horst; Graff, Andreas; Dauphin, Yannicke; Zolotoyabko, Emil; Fratzl, Peter
<x xml:space="preserve">Abstract</x> The discovery of a perfectly ordered 3D mesoporous protein/silica structure in the axial filament of the marine sponge Monorhaphis chuni is reported by I. Zlotnikov and co‐workers on page 1682. The structure belongs to a body‐centered tetragonal symmetry system and comprises interconnecting lattices of protein (red) and silica (green), templated by the self‐assembled, enzymatically active protein silicatein, whose primary function is the precipitation of silica. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>